Mental Health in Persons With Chronic Myeloid Leukemia During the SARS-CoV-2 Pandemic: The Need for Increased Access to Health Care Services - Bao, Mei; Yang, Sen; Gale, Robert Peter; Zhang, Yanli; Liu, Xiaoli; Zhu, Huanling; Liang, Rong; Liu, Bingcheng; Zhou, Li; Li, Zongru; Dou, Xuelin; Shi, Dayu; et al. (Frontiers in Psychiatry, 2021)
Mental health problems in general population has been reported during the SARS-CoV-2 pandemic, however, there were rare data in persons with chronic myeloid leukaemia (CML). Therefore, we performed a cross-sectional study on mental health evaluated using PHQ-9 (depression), GAD-7 (anxiety), and IES-R (distress) including sub-scales of avoidance, intrusion and hyper-arousal in persons with CML, non-cancer persons and immediate family members of persons with cancer as controls (≥ 16 years) by online survey. Data from 3197 persons with CML and 7256 controls were collected. In multi-variable analyses, CML was significantly-associated with moderate to severe depression (OR = 1.6; 95% Confidence Interval [CI], 1.4, 1.9; p < 0.001), anxiety (OR = 1.4 [1.1, 1.7]; p = 0.001), distress (OR = 1.3 [1.1, 1.5]; p < 0.001) and hyper-arousal (OR = 1.5 [1.3, 1.6]; p < 0.001). Moreover, delays in regular monitoring was significantly-associated with depression (OR 1.3 [1.0, 1.7]; p = 0.024), anxiety (OR = 1.3 [1.0, 1.8]; p = 0.044), avoidance (OR = 1.2 [1.0, 1.4]; p = 0.017) and intrusion (OR = 1.2 [1.0, 1.4]; p = 0.057); tyrosine kinase-inhibitor dose reduction or discontinuation, depression (OR = 1.9 [1.3, 2.8]; p = 0.001), distress (OR = 2.0 [1.4, 2.8]; p < 0.001), avoidance (OR = 1.6 [1.2, 2.1]; p = 0.004), intrusion (OR = 1.6 [1.1, 2.1]; p = 0.006) and hyper-arousal (OR = 1.3 [1.0, 1.8]; p = 0.088). We concluded that persons with CML during the SARS-CoV-2 pandemic have worse mental health including depression, anxiety and distress symptoms. Decreasing or stopping monitoring or dose resulted in adverse mental health consequences.